Developing English for Food and Beverage Service Course Materioals for D3 Perhotelan, Universitas Pendidikan Ganesha - Riasa, I.M.L. (Universitas Pendidikan Ganesha, 2018)
This study aimed at developing English for food and beverage service (ESP3) course materials for the third semester students of DIII Perhotelan at Universitas Pendidikan Ganesha. This study was designed in the form of research and development (R&D) by Sugiyono (2010) design which has several stages to be implemented namely potency and problem, data collection, product design, design validation, design revision, product trying out, product revision. The materials needed were identified based on observation, questionnaire, interview, and document analysis. The focus of the analysis was on the students’ target needs. Some students of class A were the sample in this study which were chosen by using purposive sampling. The study found the profile of materials needed by the students and there were ten topics needed namely greeting and introduction, application letter, food and beverage department, product knowledge, menu knowledge, kitchen knowledge, welcoming and taking order, handling reservation, clearing table and presenting bill, and handling complaint. The topics were developed into materials unit and each unit was divided into input, content focus, language focus, and task as suggested by Hutchinson and Waters (1987) in their theory of English for Specific purposes (ESP) design material. Formula of scale values in evaluating the appropriateness of the materials proposed by Cadiasa’s (2010) was used to know the quality of the developed materials. The result showed that the quality of the developed materials in the form of textbook was good. Thus, the material was good to be used as teaching and learning materials for the third semester students of DIII Perhotelan at Universitas Pendidikan Ganesha.